The computerization program and the delivery of services at GSIS Bacolod City - Luceño, Josiery; Miralles, Queny Roselle; Segovia, Riza; Uhlmann, Ma. Theresa
This paper attempts to determine the effect of the GSIS Computerization Program on the delivery of services among its members in Bacolod City. Using sets of data obtained from the interview schedule during the period covered by the study reveals that despite several flaws on GCP implementation, GSIS members still believe that the program will result to effective and efficient delivery of service among its members. Findings show that the program was well disseminated but failed to maintain accuracy of updates. It did not result to timely delivery of services among its members. Moreover, the problems regarding the availment of loans are prevalent.